Development of an Android-Based Reward System to Enhance the Activity of Learning - Basori Basori; Ratih Isnaini; Anisa Setyowati; Deuansvanh Phommavongsa (Jurnal Pendidikan Teknologi dan Kejuruan, 2018)
The students’ learning activity is an influential factor in the success of learning. New technology can be used to design applications to facilitate the learning process. The objectives of this study were (1) to produce a reward application system to improve the students’ activity, (2) to examine the feasibility of the developed application, and (3) to analyse the difference and the effectiveness of the application in learning compared to conventional learning. This study used the development research method adopting the 4D (define, design, develop, disseminate) model. The application was tested using ISO 25010 standards by media experts, teachers, and ten students of class X Axioo in Vocational High School also known as Sekolah Menengah Kejuruan Negeri 5 Surakarta. The effectiveness was tested using an experimental design. This study produced a proper and an efficient reward system application. The feasibility of the application for functionality, portability, usability and efficiency were 100%, 100%, 86.2% and 77% respectively. The results showed different effectiveness in learning activities between learning using the reward system application and using the conventional model.